PENGEMBANGAN MEDIA INTERAKTIF KARTU KATA UNTUK KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS 1 SD - Mila Uqtufia; Prasena Arisyanto; Yusuf Setia Wardana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to develop an interactive word card media to enhance beginning reading skills of first-grade elementary school students. The research subjects were first-grade students at SD Negeri 1 Patukangan. The method used was Research and Development (R&D) employing the ADDIE model, which consists of the stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection was conducted through observation, interviews, and validation questionnaires from media experts and material experts, as well as response questionnaires from teachers and students. The validation results indicated that the interactive word card media was highly valid, with a validity percentage of 97.5% from media experts and 98% from material experts. The practicality of the media was also rated highly, with responses of 95% from teachers and 100% from students, indicating that the media is easy to use and meets the learning needs. It can be concluded that the interactive word card media is valid and practical for use in teaching beginning reading to first-grade students. Further research is recommended to expand the media to cover broader material, different grade levels, or other subjects, as well as to test its effectiveness in various school contexts.